The chronology of the Kura-Araxes: New data and old problems of periodization and chronology of the Early Bronze Age materials in Armenia - Badalyan, Ruben (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
In a recent article I defined my concept for the periodization and chronology of the Kura-Araxes in Armenia, the main provisions of which are as follows: The Kura-Araxes sequence had a discrete character. Its periodization can be dated between 3600/3500–2900 (KA I) and 2900–2600/2500 (KA II) BC. The distinction of the Kura-Araxes phenomenon is reflected in the largely single-layered character of both early (KA I) and late (KA II) settlements: a destroyed layer demonstrates the discontinuity of certain multi-layered (KA I-II) settlements. The KA I phase represented throughout Armenia is marked by ‘Elar-Aragats’ type ceramics, which belong to a rather homogeneous complex, widespread almost all over the Armenian Highland. The homogeneity of the complex disintegrates around 2900 BC, and a mosaic of local ceramic styles follows. The KA II phase contains a series of ceramic complexes similar in basic characteristics, but stylistically rather specific. Today throughout Armenian territory there are at least three synchronous complexes, whose areas correspond to physical-geographical regions of the country: the ‘Shresh-Mokhrablur’ complex in the central part of Ararat valley, ‘Karnut-Shengavit’ to the north and east (Aragatsotn, Shirak, Kotayk, and Lori-Pambak regions), and ‘Ayrum-Teghut’ in the basins of the Aghstev and Debed rivers. Newly obtained data and my observations correspond to the above provisions. This research allows us to complement and flesh out some of them, particularly the periodization of the first period of the Kura-Araxes and a list of local variations of the KA II ceramic complexes.